Redesign of a News Portal Website Using UCD and SUS Evaluation - Widhiana, Ida Bagus Ari; Astuti, Luh Gede; Putra, I Gusti Ngurah Anom Cahyadi; Wibawa, I Gede Arta (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 14 No 1 (2025): JELIKU Volume 14 No 1, August 2025 - Preliminary Edition (Expected Completion: August 31, 2025), 2025)
Online news portals are a key source of public information in the digital era. An initial evaluation of the XYZ website revealed usability issues, including a poor interface, weak search functionality, and ineffective news recommendations. This study aimed to improve the website’s usability through a redesign using the User Centered Design (UCD) approach, evaluated with the System Usability Scale (SUS) across three stages: UT1 (initial), UT2 (after redesign), and UT3 (after implementation). Usability scores improved consistently from 58.83% (UT1) to 72.33% (UT2) and 74.83% (UT3). To enhance content relevance, TF-IDF and Cosine Similarity algorithms were implemented for news recommendations. During UT3, the recommendation feature was evaluated using Likert-scale questions, yielding an average score of 4.56 out of 5. The results indicate that integrating UCD with algorithmic recommendation systems can effectively enhance both usability and content relevance. This study demonstrates the importance of combining user-centered design principles and intelligent content filtering to improve the overall user experience on digital news platforms.   Keywords : News Portal, Redesign, User Centered Design, System Usability Scale, TF-IDF, Cosine Similarity